The role of the social worker in dealing with family disintegration - Al-Ahmadi, Sarah Hamid (Journal of Humanities & Social Sciences, 2023)
The study aimed to study the role of the social worker in facing family disintegration and its impact on the upbringing of children in Saudi society; As well as achieving the following sub-objectives:Identifying the role of the social worker in reducing the phenomenon of family disintegration; Identify the factors and causes of family disintegration; Reaching a proposed vision to improve the performance of the social worker in facing the phenomenon of family disintegration.To achieve the study objectives, the researcher used the descriptive analytical method, And the questionnaire as a study tool, which consisted of (30) phrases, was divided into three axes, and the study population consisted of all social workers working in Jeddah governorate; After the field application, the researcher obtained (60) valid questionnaires for statistical analysis.The study reached a number of results, the most prominent of which are:-The results showed that the prevailing opinion of the majority of the study sample members agree that the social worker can play a significant role in reducing the phenomenon of family disintegration.-The results showed that the prevailing opinion of the majority of the study sample is that they agree that there are factors and reasons for family disintegration.-The results showed that the prevailing opinion of the majority of the study sample members agreed on the effect of family disintegration on the upbringing of children within the family.
Keywords: Social worker; family disintegration; socialization